Association with Imidazole in the Cooperative Order–Disorder Transition in Aqueous Solution of Schizophyllan - Yoshiba, Kazuto; Yasuda, Yota; Christensen, Bjørn E; Kondo, Chisaki; Miyazaki, Yuji; Nakano, Motohiro (Langmuir, 2022)
Schizophyllan, a triple helical polysaccharide, exhibits cooperative order–disorder transition (CODT) in aqueous solutions. The transition transforms the ordered structure (triple helix I) formed between the branched side chains and solvent molecules into the disordered structure (triple helix II) without dissociation of the triple helix. The CODT behaviors in H2O–imidazole mixtures containing HCl with different molar ratios of imidazole/HCl were investigated by adiabatic calorimetry and differential scanning calorimetry on two schizophyllan solutions with different molar masses. The transition temperature (T r) and the transition enthalpy (ΔH r) significantly depended on both of the mole fractions of imidazole and imidazole/HCl. The composition dependences of T r and ΔH r in H2O–imidazole mixtures were analyzed with linear cooperative transition theory for the solvent-stabilizing effect in the mixture with active compounds. Theoretical analyses confirmed that both imidazole and imidazolium ions in the solutions competitively interact with the side chain of the triple helix.